Kajian Tematik Ayat-Ayat Mengenai Degradasi, Konservasi, dan Etika Lingkungan - Irsan, Irsan; Abubakar, Achmad; Parhani, Aan (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2021)
The environmental crisis, which is increasingly complex and has become a global problem, must immediately find a way out, including by starting to think about the relationship between humans and the environment from the perspective of Islam. The study of interpretation is an effort to explore the insight of the al-quran related to the environment, which contains warnings about environmental damage and the importance of preserving the environment. The research method used in this paper is a qualitative descriptive approach. as for the literature review with data sources used such as books, journals, articles and various relevant sources on ecology. As in Islam, humans are God's representatives on earth, so in utilizing natural resources there are instructions to always maintain their balance and prosper them. For this reason, Muslims in understanding the message of the Koran are woven with an environmental ethic or ecological awareness that is inherent as a religious practice.